17-6x+3x-5=x+11

Simple and best practice solution for 17-6x+3x-5=x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17-6x+3x-5=x+11 equation:


Simplifying
17 + -6x + 3x + -5 = x + 11

Reorder the terms:
17 + -5 + -6x + 3x = x + 11

Combine like terms: 17 + -5 = 12
12 + -6x + 3x = x + 11

Combine like terms: -6x + 3x = -3x
12 + -3x = x + 11

Reorder the terms:
12 + -3x = 11 + x

Solving
12 + -3x = 11 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
12 + -3x + -1x = 11 + x + -1x

Combine like terms: -3x + -1x = -4x
12 + -4x = 11 + x + -1x

Combine like terms: x + -1x = 0
12 + -4x = 11 + 0
12 + -4x = 11

Add '-12' to each side of the equation.
12 + -12 + -4x = 11 + -12

Combine like terms: 12 + -12 = 0
0 + -4x = 11 + -12
-4x = 11 + -12

Combine like terms: 11 + -12 = -1
-4x = -1

Divide each side by '-4'.
x = 0.25

Simplifying
x = 0.25

See similar equations:

| 6+16x=17x+2 | | 5h=7h+8 | | 24.3=14.4+2a | | 18a-7= | | 6=-5d+11 | | 10x-14-6x=18 | | 2(2x+5)=4 | | 4z-4=10 | | 9x+16=6x+106 | | 10p^2-90p=0 | | x-75x=6x | | 0.5x+0.3=1.2 | | 5(12-x)=25 | | 2x(8x-5)=(5-4x)2 | | 15y^3-123y^2+24y= | | 2x+5+2x=1 | | 7y=-19y+2 | | 15+5(3c-2)= | | -6(8x-3)=-36+6x | | 5(a+4)+3(6a-7)= | | 4x-3=-2x+27 | | 12x+162=15x | | 25+30v+26+21v=37v+11v | | 3x+9=6x-3(x+3) | | 3(x+2)=5(x-3)-13 | | 12-7n=6(n-4)-4n | | 8-2n+2n=8 | | 111-5v=71 | | 24.3=2I+2a | | 6x+8+16=10x | | 2x+4+5x-8=90 | | -2(3x-1)=-4-3x |

Equations solver categories